Aplicación de una auditoría tributaria en la empresa de servicios wasalban cía. ltda. en el cantón Latacunga provincia de Cotopaxi, en el período comprendido enero - diciembre 2011 - Taco Maigua, Blanca Targelia (2015)
This study consists of a tax audit at „Wasalban‟ Limited Company in fiscal 2011. The Company was created by Engineer Washington Albán and it is required to maintain accounting records from March 2011. The Company has management, administrative, financial, and technical department. Thanks to it the study is feasible. On the other hand, the Company had a delay with monthly tax declarations. According to the organizational structure of the Company each department has clearly defined its objectives, principles, and values which let accomplish all the processes and decisions that must be approved by the manager. In addition, micro and macro environmental factors were determined, the ones that affect direct or indirectly to the Company….